The Reasonableness of the Internal Oversight Budget of the XYZ Regional Government - Yuanita, Rizka Dytia; Wijayanti, Nanda Ayu (Jurnal Ilmiah Ilmu Administrasi Publik, 2025)
The objectives of this study is to assess assess the reasonableness of the internal supervision activity budget in the regional government of XYZ through activity based costing with statistical quality control. This research adopts a descriptive qualitative methodology using a case study approach, involving document review and interviews as data collection techniques. The analysis are applied to conduct activity-based costing (ABC) and to establish a reasonable budget range using statistical quality control methods. The study establishes threshold values for the reasonable allocation of budgets across various internal supervision activities. Based on the analysis, four activities were found to have budgets within the reasonable range, whereas three activities were identified as having insufficient (underfinanced) budget allocations. The results indicate that internal supervision budgets can be classified into reasonable and underfinanced categories. This study provides practical implications for regional governments, particularly in formulating budgetary guidelines and performing standard spending analyses to support the evaluation of budget appropriateness.